Do rural highways narrow Chinese farmers’ income gap among provinces? - Yan-zhen WENG; Ya-ting ZENG; Wen-sheng LIN (Journal of Integrative Agriculture, 2021)
To achieve complete poverty alleviation, the improvement of infrastructure and living conditions is fundamental. Promoting the flow of factors through infrastructure investment, thereby reducing the income gap among residents, has become an important focus of poverty alleviation. Because of the high amount of investment in transportation infrastructure, greater attention has been paid to the income distribution effect it brings, but few studies have analysed the effect of rural highways on the income gap of farmers. Based on the panel data pertaining to 30 provinces in China from 1993 to 2013, this paper uses a fixed-effect model to test the impact of rural highways supply on the income gap of farmers. The empirical results show that: (1) The effect of Chinese rural highways on the farmers’ income gap among provinces is “U-shaped”. (2) Chinese national and provincial trunk highways are helpful in narrowing the farmers’ income gap among provinces. (3) The level of education, household productive fixed assets investment, level of urbanization, and level of regional economic development have multiple effects on the farmers’ income gap among provinces. Then, based on the empirical analysis, the paper analyzes the mechanism of rural highways affecting the income gap of farmers from a theoretical perspective and focuses on the causes of the “U-shaped” relationship between rural highways supply and farmers’ income gap.